Предмет: Алгебра,
автор: kishinecroma2
Помогить решить
Дано
Приложения:
Ответы
Автор ответа:
0
y(x) = корень( 5x^2+4x-1)
y(x=5) = корень( 5*5^2+4*5-1) = корень(144)=12
y`(x) = 1/2*1/корень( 5x^2+4x-1)*(10x+4)
y`(x=5) = 1/2*1/корень( 5*5^2+4*5-1)*(10*5+4)= 1/2*1/12*54=54/24=9/4
dy=y`*dx
y(x2)~y(x1)+y`(x1)*(x2-x1)
y(5,08)~y(5)+y`(5)*(5,08-5)=12+9/4*0,08= 12,18
y(5,08)~12,18
y(x=5) = корень( 5*5^2+4*5-1) = корень(144)=12
y`(x) = 1/2*1/корень( 5x^2+4x-1)*(10x+4)
y`(x=5) = 1/2*1/корень( 5*5^2+4*5-1)*(10*5+4)= 1/2*1/12*54=54/24=9/4
dy=y`*dx
y(x2)~y(x1)+y`(x1)*(x2-x1)
y(5,08)~y(5)+y`(5)*(5,08-5)=12+9/4*0,08= 12,18
y(5,08)~12,18
Похожие вопросы
Предмет: Русский язык,
автор: Olzhas20031
Предмет: Русский язык,
автор: 345Summer345
Предмет: Русский язык,
автор: карина1298йбга
Предмет: Қазақ тiлi,
автор: malika5988
Предмет: Алгебра,
автор: ClarisVerbis